PHENOMENAL, SUBJECTIVE, SELF-AWARE: A CLEAR DISTINCTION WITH A VIEW TO AUGMENTED SENSORY MODALITIES - Andrade, Daniel; Chagas, Eduardo (Revista Dialectus - Revista de Filosofia, 2024)
This paper aims to analyze the concepts of phenomenal experiences, subjective standpoints, and self-awareness in light of an enactive approach to mind. In doing so, it assumes that a clear-cut reorganization of those three concepts will help to deal more safely with technological enhancements of sensory modalities, including the hypothetical introspection of a person’s own neural states. It argues in favor of understanding the mental as a subcategory of the physical and of considering measurement scales and mutually complementary perspectives while tackling the mind-body relation. After discussing realistic prospects of sensory enhancement, it explores the overlaps of the notions of phenomenal experiences, subjective standpoints, and self-awareness, concluding for a reorganization that seems convenient to understand new neurotechnologies more effectively.